2010
DOI: 10.1007/s11468-010-9125-z
|View full text |Cite
|
Sign up to set email alerts
|

UV-Vis-NIR Laser Desorption/Ionization of Synthetic Polymers Assisted by Gold Nanospheres, Nanorods and Nanostars

Abstract: The laser desorption/ionization (LDI) assisted by gold nanospheres, nanorods and nanostars has been investigated. Laser fluence thresholds for the appearance of cationized adducts of a polydispersed polyether standard (polyethylenglycol PEG600) have been determined at the near ultraviolet-visible-near infrared wavelengths delivered by a Nd:YAG laser (266, 355, 532, 1,064 nm). The results demonstrate the efficiency of surface plasmon excitation to assist laser desorption/ionizaton at laser wavelengths extending… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 41 publications
(65 reference statements)
0
22
0
Order By: Relevance
“…84 Gámez et al investigated SALDI-MS with Au nanospheres, nanorods, and nanostars at four wavelengths covering the UV, visible, and near-infrared ranges. 85 A close correlation was found between the plasmonic excitation of the NPs and the LDI thresholds.…”
Section: -85mentioning
confidence: 70%
“…84 Gámez et al investigated SALDI-MS with Au nanospheres, nanorods, and nanostars at four wavelengths covering the UV, visible, and near-infrared ranges. 85 A close correlation was found between the plasmonic excitation of the NPs and the LDI thresholds.…”
Section: -85mentioning
confidence: 70%
“…When nanoparticles are irradiated with laser energy, the PPTT property successfully transduces photon energy into heat surrounding each nanoparticle that leads to cell damage and cancer cell killing . Using NSs for photothermal cancer therapy was first mentioned in the literature by Gámez et al Later, Lu et al and Yuan et al applied star‐shaped nanoparticles to PTT for the first time in vitro and in vivo , respectively . Using TAT‐peptide functionalized NSs, our group achieved photothermolysis under 0.2 W cm −1 , which is the lowest irradiance ever reported for use in PPTT .…”
Section: Multimodality Sensing and Therapy: Sers Tpl And Photothermmentioning
confidence: 92%
“…In particular, the role of different shapes (spheres, rods, and stars) of AuNPs [75] as well as the role of morphology of Pd [79] (Figure 9) and Pt nanostructured materials [87,88] were investigated. Several groups also carried out similar works on Si-based materials [81,82,89].…”
Section: Other Aspects Influencing Desorption/ionization Mechanismsmentioning
confidence: 99%
“…Besides the importance of NP size [ 59 , 72 ] and composition [ 60 ], discussed in the previous section, other factors have been reported to influence the LDI process. Since the early appearance of nanostructures for MS applications, it was shown that surface plasmon (SP) excitation could enhance both the electromagnetic field and the charge transfer between the NP and the adsorbate molecules [ 73 ], thus affecting both desorption and ionization phenomena [ 59 , 74 , 75 ]. Such correlation was deeply studied for gold nanostructures, demonstrating that a visible laser at 532 nm, which can be resonantly absorbed by AuNPs (SP band falling in the 500 nm–600 nm range), positively affects analyte detection [ 74 , 75 , 76 , 77 ], provided that no aggregation phenomena occur.…”
Section: Other Aspects Influencing Desorption/ionization Mechanismmentioning
confidence: 99%
See 1 more Smart Citation